Approval of unit rates of non-schedule item 'Rebar Welding with Existing Rebar of D-Wall for Constructing Permanent Capping Beam' - Brac University (Brac University, 2023)
This record consists of general correspondence regarding approval of unit rates of non-schedule item 'Rebar Welding with Existing Rebar of D-Wall for Constructing Permanent Capping Beam' of BRAC University new campus project.